Difference and alteration in pharmacokinetic and metabolic characteristics of low-solubility natural medicines. (3rd April 2018) - Yan, Shenglei; Liu, Yuying; Feng, Jianfang; Zhao, Hua; Yu, Zhongshu; Zhao, Jing; Li, Yao; Zhang, Jingqing
Abstract: Drug metabolism plays vital roles in the absorption and pharmacological activity of poorly soluble natural medicines. It is important to choose suitable delivery systems to increase the bioavailability and bioactivity of natural medicines with low solubility by regulating their metabolism and pharmacokinetics. This review investigates recent developments about the metabolic and pharmacokinetic behavior of poorly soluble natural medicines and their delivery systems. Delivery systems, dosage, administration route and drug–drug interactions alter the metabolic pathway, and bioavailability of low-solubility natural medicines to different degrees. Influencing factors such as formulation, dosage, and administration route are discussed. The metabolic reactions, metabolic enzymes, metabolites and pharmacokinetic behaviors of low-solubility natural medicines, and their delivery systems are systematically reviewed. There are various metabolic situations in the case of low-solubility natural medicines. CYP3A4 and CYP2C are the most common metabolic enzymes, and hydroxylation is the most common metabolic reaction of low solubility natural medicines. The stereo isomeric configuration can have a large influence on metabolism. This review will be useful for physicians and pharmacists to guide more accurate treatment with low-solubility natural medicines by increasing drug efficacies and protecting patients from toxic side effects.